2017
DOI: 10.1371/journal.pone.0173350
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific variation in gene expression from Symbiodinium spp. associated with offshore and inshore Porites astreoides in the lower Florida Keys is lost with bleaching and disease stress

Abstract: Scleractinian coral are experiencing unprecedented rates of mortality due to increases in sea surface temperatures in response to global climate change. Some coral species however, survive high temperature events due to a reduced susceptibility to bleaching. We investigated the relationship between bleaching susceptibility and expression of five metabolically related genes of Symbiodinium spp. from the coral Porites astreoides originating from an inshore and offshore reef in the Florida Keys. The acclimatizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…This is so even despite few individual proteins differing in concentration between corals from upwelling and non-upwelling reefs. Such upwelling reef vs. non-upwelling coral proteomic differences were maintained even after one week of exposure to a non-native temperature regime (in half the cases); in other words, the concentrations of numerous proteins showed “site fidelity.” Others have documented site fidelity in coral [ 47 ] and Symbiodiniaceae [ 48 , 49 , 50 , 51 , 52 ] gene expression patterns, which can persist even across large spatio-temporal scales [ 53 ]. Since corals herein were only maintained in laboratory aquarium culture for several weeks (including the acclimation period), it would be interesting to see if such site fidelity is eventually lost after longer periods of time in a common garden setting or if these site-associated proteome-scale differences are truly entrained in their biology.…”
Section: Discussionmentioning
confidence: 99%
“…This is so even despite few individual proteins differing in concentration between corals from upwelling and non-upwelling reefs. Such upwelling reef vs. non-upwelling coral proteomic differences were maintained even after one week of exposure to a non-native temperature regime (in half the cases); in other words, the concentrations of numerous proteins showed “site fidelity.” Others have documented site fidelity in coral [ 47 ] and Symbiodiniaceae [ 48 , 49 , 50 , 51 , 52 ] gene expression patterns, which can persist even across large spatio-temporal scales [ 53 ]. Since corals herein were only maintained in laboratory aquarium culture for several weeks (including the acclimation period), it would be interesting to see if such site fidelity is eventually lost after longer periods of time in a common garden setting or if these site-associated proteome-scale differences are truly entrained in their biology.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our assumptions, Kenkel et al [20,23] observed very little gene flow between inshore and offshore populations of Porites astreoides inhabiting the FRT. Similarly, Hauff-Salas et al [46] observed collection site-specific responses in the zooxanthellae.…”
Section: Adaptive Response To Immune System Activation: Acap2 Expressionmentioning
confidence: 83%
“…Coral fragments were processed as previously described [46]. Briefly, excess skeletal fragments were removed after first pulverizing fragments into smaller pieces in LN 2 with a dounce-style stainless steel homogenizer, and the remaining tissue sample ground using a ceramic mortar and pestle.…”
Section: Sample Processing and Rna Isolationmentioning
confidence: 99%
See 2 more Smart Citations